Religion and ethnocentrism : an empirical-theological study - Capucao, Dave Dean, 1965- (Empirical Studies in Theology, 2010)
Previous studies reveal that religion, despite its ideal of solidarity, hospitality and compassion, has been the primary origin of ethnocentrism. However, other researches dispute this sweeping claim by indicating several other factors that affect this complex relationship. This empirical-theological study is an endeavour to dig deeper into these factors by examining the extent to which a number of religious images which are culled from five religious themes, namely, God, Jesus, Spirit, salvation and church, contribute to ethnocentrism. It situates these religious attitudes within the framework of the Dutch civil religion, and the different reactions to it by contemporary Dutch catholic believers.